2018
DOI: 10.1038/s41598-018-30074-9
|View full text |Cite
|
Sign up to set email alerts
|

Regional differences in thermal adaptation of a cold-water fish Rhynchocypris oxycephalus revealed by thermal tolerance and transcriptomic responses

Abstract: Understanding how populations adapt to different thermal environments is an important issue for biodiversity conservation in the context of recent global warming. To test the hypothesis that populations from southern region are more sensitive to climate change than northern region in cold-water species, we determined the thermal tolerance of two geographical populations of a cold-water fish, Rhynchocypris oxycephalus: the Hangzhou population from southern region and the Gaizhou population from northern region,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 70 publications
2
17
0
Order By: Relevance
“…Since there are differences between males and other sex/castes in body size and physiology, further studies on queens and workers should be conducted to compare thermal sensitivity between castes in social bees. Local adaptation at a large spatial scale is also possible like it was demonstrated in other organisms (Schoville et al 2012;Yu et al 2018;Collier et al 2019). However, as suggested by our results, there is no significative relation between body size of males (ITD), collecting sites, and the corresponding THS recorded for the specimen.…”
Section: Bumblebee Conservationsupporting
confidence: 76%
“…Since there are differences between males and other sex/castes in body size and physiology, further studies on queens and workers should be conducted to compare thermal sensitivity between castes in social bees. Local adaptation at a large spatial scale is also possible like it was demonstrated in other organisms (Schoville et al 2012;Yu et al 2018;Collier et al 2019). However, as suggested by our results, there is no significative relation between body size of males (ITD), collecting sites, and the corresponding THS recorded for the specimen.…”
Section: Bumblebee Conservationsupporting
confidence: 76%
“…In contrast, other studies suggest northern populations are more tolerant of high temperatures (e.g. Gaitán‐Espitia et al., 2014; Yu et al., 2018), and even still, others have found no evidence for thermal adaptation among populations (reviewed in Elliot & Elliot, 2010). The climatic variability hypothesis (Levins, 1969; Stevens, 1989) predicts that individuals at higher latitudes have greater physiological plasticity, because they experience a broader range of temperature variation.…”
Section: Discussionmentioning
confidence: 89%
“…Heat stress induces protein unfolding, which plays an important role in promoting protein refolding by stimulating HSFs to regulate HSPs, such as HSP70 and HSP90 [10]. Additionally, HSP70 and HSP90 are the primary sensors of misfolded proteins that facilitate protein folding and prevent protein aggregation during encounters with heat stress [7,18]. Pei et al [41] reported that HSP proteins partially returned to a normal level after a nine-week recovery from heat stress in rabbit testis.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have investigated the differentially expressed genes (DEGs) during the response to heat stress in fish; for instance, gene expression of Chinese minnow from the northern region showed greater thermal tolerance than the southern species [18], and the specific regulation patterns indicated a difference between imported rainbow trout and a local breeding strain [16,19]. The thermal-tolerant rainbow trout showed higher expression levels of HSPs than the low thermal-tolerant group under heat stress in fin and gill tissues [9,20].…”
Section: Introductionmentioning
confidence: 99%